Edukasi Praktikum IPA Sederhana di Sekolah Dasar dan Menengah - Nursina Sya'bania; Apriani Megati; Falentinus Pio; Febriyanti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Learning Natural Sciences (IPA) in Indonesia has been started since children were in elementary school (SD) and continued to junior high school (SMP) and high school (SMA). Science learning in primary and secondary schools in Maumere learns more about theory, the lack of practicum carried out by students makes them unfamiliar with practicum and the use of laboratory tools and materials. The alternative offered from this problem is the provision of simple Science Practicum Education in Elementary and Middle Schools. This science practicum activity was carried out in 3 schools, namely: SDN Gembira Nangahale grades 4, 5 and 6, MTS Al-Fattah Muhammadiyah Nangahale and SMA Negeri 1 Talibura. The activities carried out were responded well by the school, teachers and students. The students who took part in this activity were also very enthusiastic and actively participated in this practicum. Thus, students can get hands-on experience in practical activities.